Multiservice radio over fiber system using optical carrier suppression and polarization multiplexing method - Mohamad Nor, Mohd Hafiz (2018)
Radio over Fiber (RoF) technology, which is a combination of wireless and optical techniques, transports wireless signals over a shared optical infrastructure. Increasing demands for bandwidth and capacity requires huge improvements on RoF systems. Thus, multiservice RoF is the way forward. Existing methods such as wavelength division multiplexing (WDM) is limited by the cost of further deployment while sub-carrier multiplexing (SCM) has intermodulation distortion (IMD) limitations. Therefore, a different approach is needed. The proposed study shows that two different services can be transmitted using a single wavelength through RoF system with the use of optical carrier suppression (OCS) and polarization multiplexing (PolMux) method. The combination of these two techniques enables multiservice RoF such as long term evolution (LTE) and wireless fidelity (WiFi) services to be transmitted simultaneously at different optical polarization axis at high frequency. The proposed system measures different scenarios and its performance. Measurements include a polarization reliability test having LTE and WiFi signals at the same frequency. Other measurement includes a back to back test with and without 10 km fiber spool before the Remote Antenna Unit (RAU). Finally, a full setup with wireless transmission at the RAU of 1 m distance is proposed. Results for all setups measured are radio frequency (RF) input power, error vector magnitude (EVM) and optical receive power (ORP). Results obtained show a good reliability performance of polarization multiplexing carrying LTE and WiFi service at each polarization axis through a 10 km single mode fiber (SMF) where a full wireless transmission was then set up transmitting at 1 m wireless distance obtaining EVM for LTE of 4.5% (frequency: 875 MHz) and WiFi of 4.6% (frequency: 200 MHz). The EVM achieved is below the limit at 8% for IEEE 802.11a code rates 2/3 and 3rd generation partnership project (3GPP) for WiFi and LTE, respectively.